1998
DOI: 10.1002/(sici)1099-0496(199804)25:4<278::aid-ppul8>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

A step in the right direction: Assessing exercise tolerance in cystic fibrosis

Abstract: Summary. Exercise tolerance may be reduced in patients with cystic fibrosis, but it is not always possible to predict this from standard lung function measurements. Formal exercise testing may, therefore, be necessary, and the test should be simple and readily available. We have developed a ''3-minute step test'' and compared it with the standard 6-minute walking test. Subjects stepped up and down a 15-cm-high single step at a rate of 30 steps per minute for 3 minutes. The effect of the step test on spirometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
2
9

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(80 citation statements)
references
References 0 publications
3
66
2
9
Order By: Relevance
“…10,35 When the search was extended to healthy or unhealthy people of any age, only eight additional studies using the Bland-Altman approach were found. [36][37][38][39][40][41][42][43] Given that physical fitness can already be considered a marker of health in this period of life, 3,6,44 information about the reliability of health-related physical fitness tests in young people is of interest. In addition, the review also shows that both cardiorespiratory fitness and muscular strength were the most studied physical fitness qualities (in 41 and 50%, respectively, of the reviewed studies), whereas data about speed-agility, coordination and flexibility in young people are lacking (used in 4-14% of the reviewed studies).…”
Section: Discussionmentioning
confidence: 99%
“…10,35 When the search was extended to healthy or unhealthy people of any age, only eight additional studies using the Bland-Altman approach were found. [36][37][38][39][40][41][42][43] Given that physical fitness can already be considered a marker of health in this period of life, 3,6,44 information about the reliability of health-related physical fitness tests in young people is of interest. In addition, the review also shows that both cardiorespiratory fitness and muscular strength were the most studied physical fitness qualities (in 41 and 50%, respectively, of the reviewed studies), whereas data about speed-agility, coordination and flexibility in young people are lacking (used in 4-14% of the reviewed studies).…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of the different step tests has been studied among patients with idiopathic pulmonary fibrosis 23 , COPD 16 , asthma 24 , or cystic fibrosis 25 . Although Swinburn et al 26 observed great variation between the four step tests conducted on patients with COPD, most studies have found the opposite (i.e., little variation between the step tests among patients with chronic lung disease 16,[23][24][25] ). In patients with COPD, the CST was highly reliable for tests conducted on the same day 16 , with an ICC of 0.99 (95% CIs=0.97 to 0.99) for NOSs.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with COPD, the CST was highly reliable for tests conducted on the same day 16 , with an ICC of 0.99 (95% CIs=0.97 to 0.99) for NOSs. Balfour-Lynn et al 25 evaluated an externally dictated (30 steps/min) 3-min step test (15-cm steps) among a subgroup of individuals with cystic fibrosis (n=12) on different days. They found that this test was reliable with regard to the evaluation of SpO 2 , HR, dyspnea perception, and NOSs in 11 of 12 individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, a simple, standardised and reproducible challenge test is needed to assess the diagnosis of asthma and EIA. The step test, a reproducible test in healthy children and cystic fibrosis patients [7,8], is used with various protocols, to evaluate physical efficiency in healthy subjects and sportsmen [9][10][11][12]. It is legally compulsory in Italy for all persons wishing to engage in competitive sports [13].…”
mentioning
confidence: 99%
“…It is legally compulsory in Italy for all persons wishing to engage in competitive sports [13]. The 3-min step test is also used to assess exercise capacity in children with cystic fibrosis [8,14,15], to evaluate the effect of a course of intravenous antibiotics on exercise tolerance [16], to study candidates for lung transplantation [17], and to determine the risk of oxygen desaturation during exercise [18].…”
mentioning
confidence: 99%